Relationship of agility with tests of specific speed in football - Bocic, D.; Bajric, S.; Ilic, N.; Goranovic, S. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The research was conducted on a sample of 52 footballers of cadet with the main goal of the research to determine the importance and magnitude of the impact of manifestations of agility on the results in tests of the specific speed of running in young footballers. Seven variables for the agility estimation were applied in the research, which represented the predictor set of variables and 4 variables for the evaluation of the specific running speed as the criterion variable. Four regression analyses were used to determine the significance of predictive variables on criterion variable. The results of the regression analysis indicate that the system of predictive variables that was represented by the agility tests had achieved statistically significant influence on the results in the tests of the specific running speed with a high and significant coefficient of multiple correlation at the level of statistical significance p = .01 i p = .05.